Prognostic factors of brain metastasis and survival among HER2-positive metastatic breast ﻿cancer patients: a systematic literature review - Michelle D. Hackshaw; Heather E. Danysh; Mackenzie Henderson; Eric Wang; Nora Tu; Zahidul Islam; Amy Ladner; Mary E. Ritchey; Maribel Salas (2021)
Abstract Background Patients with breast cancer who overexpress the human epidermal growth factor receptor 2 (HER2) and subsequently develop brain metastasis (BM) typically experience poor quality of life and low survival. We conducted a comprehensive literature review to identify prognostic factors for BM and predictors of survival after developing BM, and the effects of therapies with different mechanisms of action among patients with HER2+ breast cancer (BC). Methods A prespecified search strategy was used to identify research studies investigating BM in patients with HER2+ BC published in English during January 1, 2009–to June 25, 2021. Articles were screened using a two-phase process, and data from selected articles were extracted. Results We identified 25 published articles including 4097 patients with HER2+ BC and BM. Prognostic factors associated with shorter time to BM diagnosis after initial BC diagnosis included younger age, hormone receptor negative status, larger tumor size or higher tumor grade, and lack of treatment with anti-HER2 therapy. Factors predictive of longer survival after BM included having fewer brain lesions (< 3 or a single lesion) and receipt of any treatment after BM, including radiosurgery, neurosurgery and/or systemic therapy. Patients receiving combination trastuzumab and lapatinib therapy or trastuzumab and pertuzumab therapy had the longest median survival compared with other therapies assessed in this review. Conclusions More research is needed to better understand risk factors for BM and survival after BM in the context of HER2+ BC, as well as the assessment of new anti-HER2 therapy regimens that may provide additional therapeutic options for BM in these patients.